Platelet aggregation at discharge: A useful tool in acute coronary syndromes? - Rogério Teixeira; Pedro Monteiro; Gilberto Marques; João Mariano Pego; Margarida Lourenço; Carlos Tavares; Alda Reboredo; Sílvia Monteiro; Francisco Gonçalves; Maria J. Ferreira; Mário Freitas; Graça Ribeiro; et al. (Revista Portuguesa de Cardiologia, 2012)
Introduction: Inhibition of platelet aggregation appears two hours after the first dose of clopidogrel, becomes significant after the second dose, and progresses to a steady-state value of 55% by day seven. Low response to clopidogrel has been associated with increased risk of stent thrombosis and ischemic events, particularly in the context of stable heart disease treated by percutaneous coronary intervention. Objective: To stratify medium-term prognosis of an acute coronary syndrome (ACS) population by platelet aggregation. Methods: We performed a prospective longitudinal study of 70 patients admitted for an ACS between May and August 2009. Platelet function was assessed by ADP-induced platelet aggregation using a commercially available kit (Multiplate® analyzer) at discharge. The primary endpoint was a combined outcome of mortality, non-fatal myocardial infarction, or unstable angina, with a median follow-up of 136.0 (79.0–188.0) days. Results: The median value of platelet aggregation was 16.0 U (11.0–22.5 U) with a maximum of 41.0 U and a minimum of 4.0 U (normal value according to the manufacturer: 53–122 U). After ROC curve analysis with respect to the combined endpoint (AUC 0.72), we concluded that a value of 18.5 U conferred a sensitivity of 75.0% and a specificity of 68% to that result. We therefore created two groups based on that level: group A – platelet aggregation <18.5 U, n = 44; and group B – platelet aggregation ≥18.5 U, n = 26. The groups were similar with respect to demographic data (age 60.5 [49.0–65.0] vs. 62.0 [49.0–65.0] years, p = 0.21), previous cardiovascular history, and admission diagnosis. There were no associations between left ventricular ejection fraction, GRACE risk score, or length of hospital stay and platelet aggregation. The groups were also similar with respect to antiplatelet, anticoagulant, proton pump inhibitor (63.6 vs. 46.2%, p = 0.15) and statin therapy. The variability in platelets and hemoglobin was also similar between groups. Combined event-free survival was higher in group A (96.0 vs. 76.7%, log-rank p < 0.01). Platelet aggregation higher than 18.5 U was an independent predictor of the combined event (HR 6.75, 95% CI 1.38–32.90, p = 0.02). Conclusion: In our ACS population platelet aggregation at discharge was a predictor of medium-term prognosis. Resumo: Introdução: A inibição da agregação plaquetar pelo clopidogrel surge nas primeiras 2 horas após início da toma do fármaco e atinge um valor estável de 55% pela sétima toma. Uma fraca resposta ao clopidogrel está associada a um agravamento do prognóstico isquémico, particularmente no contexto de doença coronária estável. Objetivo: Estratificação prognóstica no contexto de uma síndrome coronária aguda (SCA) pela agregação plaquetar. População e métodos: Estudo prospetivo, longitudinal, de 70 doentes admitidos por uma SCA entre maio e agosto de 2009. A função plaquetar foi determinada pela agregação plaquetar com o ADP, com o recurso a um kit comercial (Multiplate®) à data da alta. O endpoint primário do estudo foi um resultado combinado de morte, enfarte agudo do miocárdio não fatal, e angina instável – o tempo mediano de seguimento foi de 136,0 (79,0-188,0) dias. Resultados: O resultado mediano da agregação plaquetar foi de 16,0 U (11,0-22,5 U) com um máximo de 41,0 U e mínimo de 4,0 U (valor normal de 53-122 U). Após análise da curva ROC (AUC 0,72), foi concluído que um valor de corte de 18,5 U apresentava uma sensibilidade de 75% e especificidade de 68% para o resultado primário. Foram criados 2 grupos baseados nesse valor: grupo A – agregação pelo ADP < 18,5 U, n = 44; grupo B – agregação pelo ADP ≥ 18,5 U, n = 26. Os grupos foram semelhantes relativamente a dados demográficos (idade: 60,5 [49,0-65,0] versus 62,0 [49,0-65,0] anos, p = 0,21), história cardiovascular prévia, e diagnóstico de admissão. Não existiram associações entre a fração de ejeção do ventrículo esquerdo, o score de GRACE, a duração do internamento hospitalar, e a agregação plaquetar. Os grupos foram também homogéneos relativamente à terapêutica antiagregante, anticoagulante, uso de inibidores da bomba de protões (63,6 versus 46,2%, p = 0,15) e estatinas. A variação da hemoglobina e das plaquetas durante o internamento foi também semelhante para ambos os grupos. A sobrevida livre de eventos foi superior no grupo A (96,0 versus 76,7%, Log Rank p < 0,01). Um valor de agregação plaquetar superior a 18,5 U foi um preditor independente do evento combinado (HR 6,75, IC95% 1,38-32,9, p = 0,02). Conclusão: Na população estudada a agregação plaquetar à data de alta de uma SCA foi um preditor independente de prognóstico. Keywords: Platelet aggregation, Acute coronary syndromes, Prognosis, Palavras-chave: Agregação plaquetar, Síndromes coronárias agudas, Prognóstico